RUMAH SUSUN SEWA DENGAN PENDEKATAN ARSITEKTUR EKOLOGIS DI SURAKARTA - Perdana, Andika Putra; Setyawan, Hadi; Yuliani, Sri (ARSITEKTURA, 2015)
Planning and design of the Flats with Ecological Architecture approach is motivated by the density of settlements and slums along the Boro River,Jagalan Village, Surakarta. Density of existing settlements and slum area along the river resulted in environmental degradation and reduced Jagalan Village Green Open Space, because the settlement construction is done without regard to environmental conditions, resulting in an imbalance between natural and artificial environments. Environmental damage in the Village Jagalan then compounded by the behavior of people who dump waste in the river. Based on this phenomenon occurs due to lack of sufficient density residential land settlement and imbalance between the natural and the artificial environment characterized by reduced RTH and flooding in Jagalan. The purpose of the planning and design of flats with Ecological Architecture approach is to accommodate the needs of residential Jagalan and create a balance between the environment and settlements. The approach used in the flats that takes into account the principles of planning and design of Ecology Architecture include: green buildings, building that responds to floods, waste water conservation so that waste water discharged into the river does not pollute the environment, saving energy by considering the direction of the wind and sun , and using recycled materials in the flats. The results of the planning and design of the Flats with Ecological Architecture approach is a dwelling that is in accordance with the needs of the community and environment friendly.Â Keywords: A Flats, Ecology Architecture, Prone to flooding